Hepatic, gastric, and intestinal first-pass effects of vitexin in rats. (August 2014) - Xue, He-Fei; Ying, Zhe-Ming; Zhang, Wen-Jie; Meng, Yi-Han; Ying, Xi-Xiang; Kang, Ting-Guo
Abstract Context: Recent research has demonstrated that vitexin exhibits a prominent first-pass effect. In this light, it is necessary to investigate the causes of this distinct first-pass effect. Objective: The aim of this study was to evaluate hepatic, gastric, and intestinal first-pass effects of vitexin in rats and, furthermore, to investigate the role of P-glycoprotein (P-gp) and cytochrome P450 3A (CYP3A) in the absorption and secretion of vitexin in the duodenum. Materials and methods: Vitexin was infused into rats intravenously, intraportally, intraduodenally, and intragastrically (30 mg/kg). In addition, verapamil (50 mg/kg), a common substrate/inhibitor of P-gp and CYP3A, was also instilled with vitexin into the duodenum to investigate the regulatory action of P-gp and CYP3A. The plasma concentrations of vitexin were measured by the HPLC method using hesperidin as an internal standard. Results: The hepatic, gastric, and intestinal first-pass effects of vitexin in rats were 5.2%, 31.3%, and 94.1%, respectively. In addition, the total area under the plasma concentration–time curve from zero to infinity (AUC) of the vitexin plus verapamil group and of the normal saline group was 44.9 and 39.8 μgċ min/mL, respectively. Discussion and conclusion: The intestinal first-pass effect of vitexin was considerable, and gastric and hepatic first-pass effects also contribute to the low absolute oral bioavailability of vitexin. The AUC of the vitexin plus verapamil group was slightly higher than that of the vitexin plus normal saline group (by approximately 1.13-fold), suggesting that verapamil does not play an important role in the absorption and secretion of vitexin.